External Perceptions of the Oklahoma Youth Expo's March 2020 COVID-19 Response - Bree Rosman; Quisto Settle; Nathan Smith; Morgan Pfeiffer (Journal of Applied Communications, 2023)
Livestock shows are a prevalent part of youth agricultural programs in the United States, but they are not well understood, particularly in terms of risk and crisis communication. Through in-depth qualitative interviews, this study evaluated the perceptions of Oklahoma agricultural education instructors, Extension agents, and parents of youth exhibiting at the 2020 Oklahoma Youth Expo (OYE). The onset of the COVID-19 pandemic caused the stock show to cancel in the middle of its schedule. The study evaluated perceptions of the event through the lens of crisis communication as it relates to brand reputation and crisis management. The study was guided by situational crisis communication theory. The results of the interviews indicate that OYE’s brand reputation was not harmed as a result of the crisis, and some responses indicate that participants may have increased their respect of the organization. Instead, participants directed fault toward city officials who cancelled the stock show. Future research is recommended to evaluate how other stock shows responded to the 2020 COVID-19 outbreak, as well as assessing how stock shows continued to deal with the pandemic in subsequent years.
Keywords: livestock show; youth agriculture; situational crisis communication theory; brand reputation; qualitative interviews